Pengaruh Kompetensi Pemerintah Desa, Partisipasi Masyarakat Dan Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Dana Desa (Studi Kasus Desa Di Kecamatan Ende Kabupaten Ende) - Reo, Hermanus; Ismail, Nuraini (STIE AMKOP, 2024)
The research objectives are: 1. To determine the influence of village government competence on accountability in managing village funds in Ende District, Ende Regency. 2. To determine the effect of community participation on accountability in managing village funds in Ende District, Ende Regency. 3. To determine the effect of the use of information technology on the accountability of village fund management in Ende District, Ende Regency. The research method used is a quantitative method. This research was conducted in a village in Ende District, Ende Regency. The sampling technique in this research was purposive sampling so that the sample taken was 84 people. The data collection techniques used in this research are: Observation, Interviews, Questionnaires, Documentation and Literature Study. The results of the hypothesis test can be concluded: 1. Village government competence influences the accountability of village fund management. With a value (β) the regression coefficient of the village government competency variable is 0.143 with tcount > ttable (3.002 > 1.990) and a significance level of 0.004 < 0.05. 2. Community participation influences the accountability of village fund management. With a value (β) the regression coefficient for the community participation variable is 0.149 with tcount > ttable (2.353 > 1.990) and a significance level of 0.021 < 0.05. 3. The use of information technology influences the accountability of village fund management. With a value (β) the regression coefficient for the information technology utilization variable is 0.227 with tcount > ttable (2.870 > 1.990) and a significance level of 0.005 < 0.05.